The effect of Word of Mouth (WOM) on online pricing: A case study at BizRate UK website - Ma, Chiahao (2009)
In response to the rising power of electronic word of mouth (eWOM), marketers are gradually placing importance on the effects on their marketing strategies. The main objective of the study is to use both secondary as well as primary data to investigate the relationship and interaction between eWOM and online pricing. This study took BizRate UK, a price comparison website, as the database to investigate 100 laptop and digital camera products and conducted interviews with online shoppers and managers from online retailers.